Observing Umrah Worshipping Commitment with EMAI Model (Expectation, Motivation, Attitude, and Intention) among Middle-Class Muslims through Religiosity - Arham, M. Nur; Razak, Syaparuddin; Husain, Hukmiah; Sahaka, Arifin (Review of Islamic Economics and Finance, 2024)
Purpose – This study aims to investigate the role of religiosity in the EMAI Model (Expectation, Motivation, Attitude, and Intention) in influencing Umrah worshipping commitment among middle-class Muslims.Methodology - In this study, the variables used are Umrah worshipping commitment, Umrah worshipping intention, Attitude, Religiosity, Expectation, and Motivation. This study is conducted by using data from questionnaires on South Sulawesi's middle-class Muslims in Indonesia, with 213 respondents using a Likert scale. Structural Equation Modeling (SEM) via SmartPLS 4 used to analyze the data. Findings - The results show a positive and significant correlation between Umrah worshipping intention and commitment. Attitude, Religiosity, Expectation, and Motivation positively influence Umrah worshipping intention. Attitude plays a pivotal role in shaping Umrah worshipping commitment through Intention mediation. Religiosity, Expectation, and Motivation impact Umrah worshipping intention through Attitude mediation. The study underscores Religiosity in forming Umrah worshipping commitment via the EMAI Model, highlighting its foundational role